Yellow crazy ants (Anoplolepis gracilipes [Smith, F., 1857]: Hymenoptera: Formicidae) threaten community of ground-dwelling arthropods in dry evergreen forests of Thailand - Sasitorn Hasin; Wattanachai Tasen; Mizue Ohashi; Warin Boonriam; Akinori Yamada (Agriculture and Natural Resources, 2021)
Anoplolepis gracilipes is a widespread invasive species in tropical regions, posing a serious threat to native fauna. However, there is a lack of comprehensive field investigations into the negative impact of this species on ground-dwelling arthropods (GDAs). Herein, GDA orders, native ant species, and the abundance of native ant nests were compared between invaded (IVA) and uninvaded (UVA) areas in a dry evergreen forest in the Sakaerat Biosphere Reserve, Thailand. Pitfall traps was used to collect GDAs, including ants. Ant nests were surveyed using direct sampling and food baits. In total, 8,058 GDAs belonging to 13 orders were collected from both areas. Within the IVA, the abundance levels of centipedes, isopods, spiders, cockroaches, termites, beetles and ants were lower than those in the UVA. In addition, the frequency levels of occurrence of centipedes, isopods, cockroaches and termites were lower in the IVA than in the UVA. In total, 83 species of native ants were collected, and the more diverse ant population was in the UVA (66 species) compared to the IVA (49 species). The abundance and frequency of occurrence levels of seven ant species were significantly higher in the UVA than in the IVA. In total, 4,431 nests were found. Nest abundance of native ants in four nest categories and nest occurrence in two nest categories were significantly higher in the UVA than in the IVA. These results clearly indicated that invasion of A. gracilipes adversely affected the GDA community, especially native ant species and their nest abundance and occurrence.